Hubungan Tingkat Pengetahuan dan Sikap Ibu Dengan Pemberian Vitamin A Pada Anak Balita di Wilayah Kerja Puskesmas Dadok Tunggul Hitam Kota Padang Tahun 2024 - Ningsih, Fika Mai Putri; Asyari, Dian Paramitha (Yayasan Jompa Research and Development, 2024)
Sure! Here’s the translation: — The coverage of vitamin A supplementation in the Padang City Health Office in 2022 was 65.5%, with a target of 100%. The aim of this research is to determine the relationship between mothers' knowledge and attitudes toward vitamin A supplementation for toddlers in the working area of the Dadok Tunggul Hitam Public Health Center in Padang City in 2024. This quantitative study uses a cross-sectional design. The research was conducted in the working area of the Dadok Tunggul Hitam Public Health Center, with a population of 2,395 mothers who have toddlers. A sample of 96 respondents was obtained using proportional random sampling. Data were collected using a questionnaire through interviews, and data analysis was performed univariately using frequency distribution and bivariately using the Chi-square test. The results showed that 76% of mothers had a poor level of knowledge about vitamin A, and 50% had a negative attitude toward vitamin A supplementation. There is a relationship between the level of knowledge (p-value = 0.044) and vitamin A supplementation for toddlers. However, mothers' attitudes did not show a significant relationship with vitamin A supplementation for toddlers in the Dadok Tunggul Hitam Public Health Center area (p-value = 0.412). In conclusion, the level of knowledge has a significant relationship with vitamin A supplementation for toddlers, while mothers' attitudes do not have a significant relationship with vitamin A supplementation for toddlers. It is hoped that nutrition officers at the Dadok Tunggul Hitam Public Health Center in Padang City can provide counseling and health promotion to mothers regarding vitamin A supplementation during every Posyandu event and visit homes of toddlers who have not received vitamin A to provide it directly. Keywords: Mothers, Toddlers, Knowledge Level, Attitude, Vitamin A